KRITERIA SAKSI DALAM MEMBERIKAN KESAKSIAN YANG BENAR PADA PERKARA PERCERAIAN DI PENGADILAN AGAMA KELAS 1A PALEMBANG - Muzakki Mursyad Adib; Duski Ibrahim; Yuswalina Yuswalina (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
This research is entitled Judge's View of Witness Criteria in Providing Correct Testimony in Divorce Cases in Palembang Class 1A Religious Court. The background of this thesis is that the witness evidence is very influential in the netting of the trial. But on the other hand that it is not uncommon for a witness to not mention what happened actually, for certain reasons. This research problem formulation. 1). What is the Judge's View of the Witness Criteria in providing actual testimony on divorce cases in Palembang's Class 1 Religious Court. 2). How is the Judge's View of the Witness Criteria in providing actual testimony on divorce cases according to Islamic Family Law. This research is the type of field research. The type of data used is qualitative data , then primary data is obtained, namely the primary data that directly interviews the judge, secondary data , obtained from several books in the library. Documentation data is carried out as related documents about the testimony in the event at the trial. After conducting this research, the conclusions can be drawn, namely: 1). The criteria for testimony in a trial in a court is to refer to the applicable procedural law in the court, and the judge's basis for trial is the content of the lawsuit. 2). The criteria in Islamic Family Law that refer to Islamic Jurisprudence is to have honesty and not cover up the truth. Keywords: Divorce, Witness, Islamic Law